Leveraging a Program Manager to Optimize Nurse Development - Shaw, Martha; Montgomery, Tiffany (Journal for nurses in professional development, 2025)
This article explores the strategic and unique role of the Nursing Professional Development (NPD) Program Manager for preceptor and mentor programs within a clinical education department. By centralizing responsibility for preceptor and mentor processes, this role reduces the operational burden on NPD practitioners, ensures program consistency, and supports a structured and standardized approach to orientation and professional growth within the nursing workforce.